Islamic Banks’ Financial Stability and Its Determinants: a Comparison Study With Conventional Banks in Indonesia - Pambuko, Zulfikar Bagus; Ichsan, Nur; Anto, MB. Hendrie (IQTISHADIA, 2018)
The research aimed to analyze the stability of Islamic banking industry and its determinants in Indonesia. The same analysis was also done to the conventional banking industry as Indonesia practices dual banking systems. Using monthly data on Indonesian Banking Statistics for 2008-2013, this research implemented the Banking Stability Index (BSI) model for predicting the bank's stability. The analysis began with measuring BSI then using VECM to examine the effect of variables on BSI. The result showed that the BSI of both banking system was exhibiting the moderate level of stability though Islamic banking is more stable and safe way of financing than conventional banking. The shocks of inflation, exchange rate, efficiency, income diversity, liquidity, and Industrial Production Index responded positively by Islamic Bank' stability, while interest rate and market share responded negatively. In another hand, conventional bank' stability responded positively the shock of the exchange rate, income diversity, interest rate, liquidity, and market share, while other variables responded negatively. The results of shocking variables strongly indicated that the conventional banking is more vulnerable than Islamic banking. Islamic banking looked tend to the shock resistance and less volatile. This conclusion, however, might be still questioned as the BSI was not designed specifically for Islamic banking. Therefore, constructing an Islamic BSI (under Islamic banking characters) was important to measure the banking stability more appropriate and to develop a proper early warning system for Islamic banking industry.